1997
DOI: 10.1046/j.1472-765x.1997.00348.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH and NaCl on growth from spores of non‐proteolytic Clostridium botulinum at chill temperature

Abstract: The effect of combinations of temperature (2°, 3°, 4°, 5°, 8° and 10°C), pH (5·0–7·2) and NaCl (0·1–5·0% w/w) on growth from spores of non‐proteolytic Clostridium botulinum types B, E and F was determined using a strictly anaerobic medium. Inoculated media were observed weekly for turbidity, and tests were made for the presence of toxin in conditions that approached the limits of growth. Growth and toxin production were detected at 3°C in 5 weeks, at 4°C in 3/4 weeks and at 5°C in 2/3 weeks. The resulting data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
64
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(71 citation statements)
references
References 2 publications
5
64
2
Order By: Relevance
“…Overall, the results of the PCR analyses indicated that very little growth occurred during the storage. Toxin production by nonproteolytic C. botulinum has been shown to occasionally occur with very weak growth or no detectable growth (6,14,24,25). It is also possible that all true C. botulinum-positive samples were not detected due to the large size of the samples and the low inoculum levels.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the results of the PCR analyses indicated that very little growth occurred during the storage. Toxin production by nonproteolytic C. botulinum has been shown to occasionally occur with very weak growth or no detectable growth (6,14,24,25). It is also possible that all true C. botulinum-positive samples were not detected due to the large size of the samples and the low inoculum levels.…”
Section: Discussionmentioning
confidence: 99%
“…many carbohydrates and, like other nonproteolytic "group II" C. botulinum strains, grow and produce toxin at temperatures as low as 3°C (6). This attribute together with anaerobic growth makes the strains particularly hazardous for refrigerated vacuum-packaged foods.…”
mentioning
confidence: 99%
“…Nonproteolytic C. botulinum is one of the two groups most frequently associated with food-borne botulism. This group produces spores which can survive pasteurization heat treatments and are able to germinate, grow, and produce toxin at 3°C (9). These characteristics make nonproteolytic C. botulinum a particular concern in the production of mild-heat-treated refrigerated foods (17).…”
mentioning
confidence: 99%